Use of hemilaminectomy in cases of spinal compression by extrusion of intervertebral disc in dogs: Review - Santos dos Santos , Jennifer; Andrade, Alisson; Freitas, Bibiana; Cardona, Rodrigo Otávio (Pubvet, 2021)
Neurology is a specialty that grows more and more in veterinary medicine, seen as neurological disorders commonly found in the clinic of small animals. However, many neurological diseases can be treated significantly. Especially when the diagnosis is made early, and the logo of the treatment started, can be clinical or surgical. One of the most common diseases that affects the central nervous system is intervertebral disc disease (Hansen type I), characterized by the extrusion of the intervertebral disc, causing neurological changes in dogs, especially in small dogs. In this case, when the treatment is surgical, there are several surgical approaches related to the literature, with a hemilaminectomy being a surgical technique most commonly used for spinal cord decompression. Thus, since it is a highly serious disease, this article aims to list the main resources of this disease and the use of the hemilaminectomy technique for its treatment, without qualifying or prognosis, depends on the degree of neurological injury associated with the postoperative period.
Keywords: Dog; extrusion; spinal cord; neurology